Prompt-based AI Use Training for Research Preparation for Beginner Researchers at the Faculty of Teacher Training and Education, Ahmad Dahlan University, Yogyakarta - Megasari, Jayanti; Azizah, Asma; Samsudin, Didin; Kurniawan, Muhammad Ardi (Jurnal Abdimas, 2025)
The use of prompt-based Artificial Intelligence (AI) has grown rapidly in academia, offering efficiency and improved research quality. However, student researchers as novice researchers still face challenges such as difficulty formulating research problems, finding and summarizing relevant academic sources, and limited skills in writing effective prompts. Furthermore, there is a lack of programs or training specifically teaching the optimal use of AI in a research context. This Community Service (PkM) was implemented to provide a comprehensive understanding of the use of prompt-based AI in the context of preparing academic research critically, creatively, and ethically, and to help students utilize it in complex research stages, such as literature searches, problem formulation, and instrument development. This activity collaborated with students from the Faculty of Teacher Training and Education at Ahmad Dahlan University (UAD) as partners. The training implementation method used a blended learning model (online and offline) and a mixed explanatory method (sequential explanatory) to measure the effectiveness of the training through quantitative data (pre- and post-training surveys) followed by qualitative exploration. The results of the activity showed a significant increase in all aspects of student research competency. Understanding of scientific research procedures improved from "quite capable" to "capable–very capable." Furthermore, their ability to formulate research problems, locate relevant references, and develop scientific article outlines also consistently strengthened. This PkM successfully equipped students to be more independently prepared to initiate and conduct undergraduate research and produced training modules that can be used continuously.